Manifestation of pityriasis rosea and pityriasis rosea‐like eruptions after Covid‐19 vaccine: A systematic review - Iman Khan; Ahmed A. Elsanousi; Amena M. Shareef; Sameer S. Tebha; Aabiya Arif; Sana Gul (Immunity, Inflammation and Disease)
Abstract Background: After introducing Covid‐19 vaccines, a few side effects were reported, pityriasis rosea being one of them. Therefore, this study will systematically review its manifestation afteradministration.Methods: Databases were searched, covering a timeline from December 1, 2019 to February 28, 2022. Data were independently extracted and accessed for bias. SPSS statistical software version 25 was used for appropriate inferential statistics. Results: Thirty‐one studies were included for data extraction after screening following the eligibility criteria. A total of 111 people were identified to have developed pityriasis rosea or pityriasis rosea‐like eruptions after vaccination, out of which 36 (55.38%) were female. The average age of incidence was calculated to be 44.92 years, and 63 (62.37%) people presented after administration of the first dose. It was found popularly in the trunk area, either asymptomatically or with mild symptoms. Meantime the onset, was 8.58 days, and meantime it took to recover, was 6.44 weeks. Conclusion: The association between pityriasis rosea and pityriasis rosea‐like eruptions after Covid‐19 vaccines was established, but given the scarcity of studies, there is a need to conduct different clinical trials to confirm this association further and study the etiology and mechanism of the disease.